Quilting Monsters with Lacan - Conroy, Melissa (The journal of gods and monsters, 2020)
This article considers the way in which human beings are displaced into the category of the monster. Specifically, I apply psychoanalyst Jacques Lacan’s quilt of the human subject to two humans who were connected overtly to monstrosity (one to demons, the other to mythical monsters), in order to "monstrify" them. Lacan’s depiction of a subject stitched into a three-layered structure of an ultimately unknowable reality (the Real), images (the Imaginary), and signification (the Symbolic), offers a psychoanalytic structure that explains the role of the monster in the creation of self and Other. Lacan’s framework provides a way to compare three aspects that individuals who are displaced into the category of the monster share: the disturbance the body causes to the mind of the observer (the Real), the use of images to produce a sense of self aligned with order and normalcy (the Imaginary), and the use of symbols and binaries to designate the categories of human and monster (the Symbolic). By viewing these bodies through Lacan’s registers, the viewer sees a body that 1) disturbs normalcy and violates the boundaries of the self, 2) is placed within the binaries that produce self and Other, human and monster, and 3) is subjected to methods whereby the monstrous element of the figure is excised, through violence of either a punitive or surgical nature, which has the dual feature of restoring the figure to the "proper" position in the human/monster binary as well as the male/female binary.